"I shut it out": expectant mothers' fear of childbirth after a traumatic birth—a phenomenological study. Issue 1 (31st December 2022) - Olsen, Barbo; Forgaard, Anikken; Nordsletta, Anne-Hedvig Salmi; Sommerseth, Eva; Røseth, Idun
ABSTRACT: Purpose: To describe expectant mothers' experiences of fear of childbirth after a previous traumatic birth. Method: Qualitative, individual, in-depth interviews were conducted with eight expectant mothers between September and November 2020. Data were analysed using a descriptive phenomenological approach. Results: We identified four interconnected constituents: Suboptimal midwifery care, loss of control and agency; insufficient time and capacity to process a traumatic birth experience; "The baby has to be delivered!", and finally, the path to a new childbirth with the hope of mastering fears. Conclusion: Findings reveal an association between a previous history of traumatic birth and a fear of childbirth in expectant mothers. The trauma they experienced whilst giving birth strongly impacted their subsequent pregnancy, making it difficult for them to deal with the new pregnancy and impending birth. Women who have experienced a traumatic birth need to have the opportunity to process the trauma. Routines must therefore be developed that identify, support and follow up with the women. If these women are identified and given the help they need, this may help prevent and/or alleviate fear of childbirth in their subsequent pregnancy.